A behavioural finance approach to working capital management. Issue 8 (14th July 2016) - Ramiah, Vikash; Zhao, Yilang; Moosa, Imad; Graham, Michael
Abstract : This paper documents the behaviour of corporate treasurers who are involved in the decision-making process in the areas of cash, inventory, accounts receivable, accounts payable and risk management during the global financial crisis. Using a survey questionnaire, we attempt to find out if working capital managers are prone to certain heuristic-driven biases, such as loss aversion, high confidence level, anchoring and self-serving biases. Our findings show that these professionals exhibit signs of behavioural biases. Although the biases lead to sub-optimal decisions in certain areas of working capital management (WCM), they can also be desirable attributes in other aspects of WCM. We propose a profile of a good working capital manager.